Cell culture-derived flu vaccine: Present and future - Alberto Pérez Rubio; Jose María Eiros (Taylor & Francis Group, 2018)
The benefit of influenza vaccines is difficult to estimate due to the complexity of accurately assessing the burden of influenza. To improve the efficacy of influenza vaccines, vaccine manufacturers have developed quadrivalent influenza vaccine (QIV) formulations for seasonal vaccination by including both influenza B lineages. Three parallel approaches for producing influenza vaccines are attracting the interest of many vaccine manufacturing companies. The first and oldest is the conventional egg-derived influenza vaccine, which is used by the current licensed influenza vaccines. The second approach is a cell culture-derived influenza vaccine, and the third and most recent is synthetic vaccines. Here, we analyze the difficulties with vaccines production in eggs and compare this to cell culture-derived influenza vaccines and discuss the future of cell culture-derived QIVs.Keywords: Influenza vaccine, cell culture-derived, quadrivalent.